Media and Globalization and their Impact on Arab Nationalism - Olaimat, Farhan; Al-Hamad, Khalf; Al-Hadeed, Ali (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to shed light on the impact of media and globalization on Arab nationalism in light of the calls and repercussions that appear from time to time in the West and the United States of America and calls for and encourages Western nationalism. The research highlights the emergence of Arab nationalism and the challenges it faced and the role of media and globalization in its way. The researcher used the qualitative analytical descriptive approach to illustrate the impact of media and globalization on Arab nationalism. As he collected and analyzed the relevant material, he used the historical approach in part of this research related to tracing the emergence of the Arab national movement. The results show that the idea of Arab nationalism dates back tens of centuries, although it took on a deeper conceptual and theoretical dimension in the last century.